Beyond Economic Growth : An Introduction to Sustainable Development, Second Edition - Soubbotina, Tatyana P. (Washington, DC: World Bank, 2013)
This book is designed primarily to help readers broaden their knowledge of global issues, gain insight into their country's situation in a global context, and understand the problems of sustaianble development--both national and global. Because development is a comprehensive process involving economic as well as social and environmental changes, this book takes an interdisciplinary approach. It attempts to describe and explain the complex relationships among various aspects of development, including population growth, economic growth, improvements in education and health, urbanization, and globalization.